ANALISIS PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DINAS PERTANIAN KOTA SURAKARTA - Retno Susanti, Nur Diniyah, Sutarno & (Universitas Slamet Riyadi, 2017)
This study aims to identify and analyze the influence of work motivation, workdiscipline, work environment, on the performance of civil servants agriculturedepartment in Surakarta. The population is all of civil servants agriculture departmentin Surakarta. 77 respondents are selected as sample, using total sampling. This researchuses census method, the type data collection with questionnaire and observation. Dataanalysis used test instruments, classic assumption test, multiple linear regressionanalysis,t test, F test, the coefficient of determination. The result is there workmotivationhave significant effect on employee performance, work discipline dont havesignifcants effect on employee performance, work environment have significant effect onemployee performance, and the results of the study also showed, that work environmentis the most dominant variables on performance. Adjusted R2 on multiple linearregression analysis is 89 percent.Keywords: work motivation, work discipline, work environment, performance